Religious Pluralism and Legal Dimensions of Interfaith Living in Besuki Village Situbondo - Ahmad Hoiri (Rechtenstudent, 2024)
This study examines the socio-religious harmony between Muslims, Christians, and Tionghoa in Besuki Village, Situbondo Regency. Despite their different religious, cultural, and ethnic backgrounds, the people of this village are able to build a harmonious and respectful life together. This harmony is realized through inclusive social interactions, tolerance, and the understanding and practice of religious teachings that uphold universal humanitarian and spiritual values. Factors supporting this harmony include an inclusive understanding of religion, religious teachings that emphasize peace, a sense of love for the homeland, and an attitude of tolerance between religious communities. However, challenges remain, such as conflicts over the establishment of houses of worship, interfaith marriages, and a weak understanding of diversity among the younger generation. This study shows that socio-religious harmony is not something that occurs naturally, but rather the result of joint efforts, collective awareness, and a commitment to living peacefully in diversity.